Nitrogen-Dopped Ordered Mesoporous Carbon Anchored Pd Nanoparticles for Solvent Free Selective Oxidation of Benzyl Alcohol to Benzaldehyde by Using O2 - Song, Hongbing; Liu, Zong; Gai, Hengjun; Wang, Yongjie; Qiao, Lin; Zhong, Caiyun; Yin, Xiangyang; Xiao, Meng (Frontiers in Chemistry, 2019)
Introducing electron-rich nitrogen atoms to ordered mesoporous carbons (OMC) as supports for noble metal catalysts, not only improves the hydrophilic properties of a mesoporous carbon surface, but also enhances the coordination and binding abilities of metal ion. In the present work, nitrogen-doped ordered mesoporous carbons (NOMCs) were successfully fabricated via a facile hydrothermal self-assembly. The prepared NOMCs were characterized through powder X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and nitrogen adsorption-desorption isotherm. The analyses demonstrated that the NOMCs prepared at a pyrolysis temperature of 750 ℃ possessed an ordered 2D hexagonal mesoporous structure, a high graphitization degree, large surface area, and a well-distributed pore size. In particular, NOMCs could anchor Pd nanoparticles uniformly because of the introducing N atoms with strong electronegativity. Which were selected as efficient catalysts for the partial oxidation of benzyl alcohol to benzaldehyde. Approximately 24.63% conversion with 85.71% selectivity to benzaldehyde was obtained without using any solvent by molecular O2 oxidation. Most importantly, the TOF value of the catalyst in the reaction system was up to 8698 h-1. After five runs reaction, TOF and selectivity of the catalyst remained essentially same. Hence, the proposed catalyst has a potential engineering application value.